2020
DOI: 10.1038/s41467-020-15771-2
|View full text |Cite
|
Sign up to set email alerts
|

Polyamide nanofiltration membrane with highly uniform sub-nanometre pores for sub-1 Å precision separation

Abstract: Separating molecules or ions with sub-Angstrom scale precision is important but technically challenging. Achieving such a precise separation using membranes requires Angstrom scale pores with a high level of pore size uniformity. Herein, we demonstrate that precise solutesolute separation can be achieved using polyamide membranes formed via surfactantassembly regulated interfacial polymerization (SARIP). The dynamic, self-assembled network of surfactants facilitates faster and more homogeneous diffusion of ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
329
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 487 publications
(346 citation statements)
references
References 33 publications
16
329
0
1
Order By: Relevance
“…[ 25 ] Polyamide nanofiltration membrane with highly uniform sub‐nanometer pores for sub‐1 Å precision separation in the single salt feed has been reported by Liang et al. [ 26 ] For this membrane, a much higher separation factor (182) between monovalent to divalent ions, with water permeance of 17.1 L m −2 h −1 bar −1 , is reported. [ 26 ] However, all synthetic membranes suffer from a trade‐off relationship between water permeance and the ion selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25 ] Polyamide nanofiltration membrane with highly uniform sub‐nanometer pores for sub‐1 Å precision separation in the single salt feed has been reported by Liang et al. [ 26 ] For this membrane, a much higher separation factor (182) between monovalent to divalent ions, with water permeance of 17.1 L m −2 h −1 bar −1 , is reported. [ 26 ] However, all synthetic membranes suffer from a trade‐off relationship between water permeance and the ion selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 proves that the PA active layer was steadily polymerized on the surface of the PES support without apparent defects. Furthermore, the sporadic protrusions on the surface of the TFC NF membranes ( Figure 3 B–D) were formed during the IP processes [ 10 ]. From the cross-section morphology of the TFC NF membranes ( Figure 3 a–d), it can be observed that the thickness of all the PA active layers was around 145 nm and did not change greatly with the monomer concentration.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the TAEA-PIP0 membrane should have had the highest MgCl 2 rejection, but the observations were completely the opposite. Thus, the salt rejection behavior of the resulting TAEA-PIP membranes depended on size-based sieving when the electro-positivity was similar [ 10 , 46 ]. Taking into account both water permeance and salt rejection, the TAEA-PIP0.01 NF membrane was selected for further studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,6,7 Membranes possess inherent attributes of high energy e ciency, good environmental safety, cost-effectiveness and small plant footprint, which exhibit grand potential for enormous separations in energy and environment elds. 8,9,10,11 However, the implementation of membranes for angstrom/sub-angstrom scale precise ion or molecule separations such as ion sieving, chiral recognition and ole n/para n separation still remains a major global challenge, 12,13,14 and the corresponding high-performance membranes are urgently needed. 15,16 Cellular membranes regulate the selective transport of sub-angstrom/angstrom scale ions or molecules with exceptional selectivity and superhigh transport rates, such as ions, water, gas and organic molecules for cell metabolism.…”
Section: Introductionmentioning
confidence: 99%